Investigating the Impact of Climate Change Mitigation Technology on the Transport Sector CO2 Emissions: Evidence From Panel Quantile Regression - Bhowmik, Roni; Rahut, Dil Bahadur; Syed, Qasim Raza (Frontiers in Environmental Science, 2022)
Carbon emissions from the transport sector (COE) has witnessed unprecedented growth, which calls for special measures to control these emissions to achieve carbon neutrality by 2050. One of the measures taken to limit these emissions is climate change mitigation technology related to the transport sector (CCMT). However, there exists relatively scant literature that explores the CCMT-COE nexus. Hence, the present study explores whether CCMT curbs COE in the top transport sector carbon-emitting countries. For this purpose, we employ a panel quantile regression (PQR) approach, which probes the impact of CCMT on COE in low-, middle, and high-emission countries. The result shows that CCMT does not affect COE at the lowest quantile (i.e., 10th quantile) while CCMT plunges the emissions at all other quantiles. In particular, a 1% increase in CCMT curbs COE by 0.13% at the 25th, 50th, and 75th quantile, while a 1% upsurge in CCMT impedes COE by 0.22% at the 90th quantile. In the light of these findings, the carbon policy in the transport sector should invest in climate change mitigating technology in the transport sector and scale it up and out.